Sustainability in Portuguese hotels : is the circular economy coming to the hospitality sector? - Diogo, Joana Coração Boavida (2024)
In 2022, Europe witnessed a substantial contribution of over 1.9 billion US dollars to the Gross Domestic Product from travel and tourism, with Portugal ranking as the third European Union country most reliant on tourism. These significant figures not only manifest in the economic returns to the destination but also in the consequential waste and emissions generated by the activity. The sector’s impact on natural resources and the environment raises concerns, especially given the current climate emergency and the demand for resources that exceeds the planet’s capacity. It has become clear that there needs to be a better use and allocation of resources. Addressing this challenge, the concepts of sustainability and Circular Economy (CE) emerge as a potential solution to mitigate the negative impacts associated with the tourism industry and its players. Considering this, the thesis explores the perception and integration of sustainability practices and CE principles in some of Portugal’s best examples of sustainable hospitality, drawing from interviews conducted with industry professionals. The primary finding of this thesis reveals that Portuguese hoteliers perceive these practices and principles as necessary and are already adopting them, mainly making use of the recycling, reusing, reducing, and repairing principles. Other relevant notions that arise from this thesis regard topics such as market differentiation, staff resistance, and the growth of “green certificates”.